Postgraduate Physical Education Program at São Judas Tadeu University, SP - Miranda, Maria Luiza de Jesus (2013)
The objective of this paper is to present the Physical Education Post-Graduation Programme from the University São Judas Tadeu, reporting the circumstances of the Master and Doctorate´s courses creation, in 2004 and 2010 respectively. In order to do this there will be a description of the objective of the programme; its curricular structure; the academic teaching staff and how the students are selected; as well as the actions to implement the scientific production both from the academic teaching staff and students; the major issues the Programme dealt with in its development, finishing off by looking ahead as regards to the orientation of Capes for Area21.